Engaging large classes of higher education students: a combination of spaced learning and team-based learning - Carlos, Vânia; Rodrigues, Mário; Matos, Bárbara; Gonçalves, Lurdes; Ribeiro, Fernando; Fardilha, Margarida (Frontiers in Education, 2023)
We are in an era where keeping students focused and interested can be challenging. Furthermore, it is relevant, in avoiding students dropping out and increasing students’ achievements, to research how student engagement can be nurtured and how this aspect is influenced by teacher attitude and the teaching and learning (T and L) approaches. With the purpose of engaging a large biochemistry class of first-year students (n = 170 in the pilot study and n = 147 in the full project) from the Biomedical Sciences degree at the University of Aveiro in Portugal, a combination of two different learning methodologies was implemented: Team-based Learning (TBL) and Spaced Learning (SL). The main objectives of this pedagogical innovation were to promote collaboration between students, keep students engaged throughout the semester, and keep the teacher satisfied through the participation of students in class and positive feedback. A typical class involved various steps which combined different facets of TBL and SL: a bibliography was provided one week in advance to the students for them to get familiarized with it; in class, the students answered an individual quiz, followed by a group quiz; the next step was solving a problem. Meanwhile, an SL break occurred in which students did distracting activities (usually physical activities). Lastly, a short seminar in the form of a Q & A occurred to clarify any doubts. The assessment of this class involved different individual and group components. Qualitative and quantitative data were collected through focus group interviews, questionnaires, and observation techniques. After analyzing the results, in general, we can conclude that students seem to prefe learning with TBL and SL than with traditional methodologies. Students emphasized the SL as a positive strategy. Furthermore, they acknowledge that teacher attitude was crucial for their engagement.